Awareness on Preventive Measures taken by Health Care Professionals Attending COVID-19 Patients among Dental Students - Princeton, Bianca; Santhakumar, Preetha; Prathap, Lavanya (European Journal of Dentistry, 2020)
Objectives Coronavirus disease is an infectious disease caused by a newly discovered coronavirus. This virus primarily spreads through droplets of saliva or discharge from the nose when an infected person coughs or sneezes. This virus was named after its shape, which takes the form of a crown with protrusions around it. The World Health Organization has recommended personal protective equipments (PPE) to doctors and health care workers attending COVID-19 patients. PPE generally includes masks, goggles, respirators, gloves, face shields, and isolation gowns. The principle aim of this study is to create awareness among dental students about the preventive measures taken by health care professionals while attending patients affected with COVID-19.Materials & Methods A questionnaire comprising 15 questions was created using an online Google forms website and was circulated among 100 dental students. The survey was conducted within a week in the months of April to May 2020. The results and observations were recorded in the form of pie charts.Results Ninety-three percent of the participants have stated that health care professionals must clean their hands often, cover their nose and mouth, and maintain safe distance from everyone in order to prevent the virus from affecting them. Sixty-three percent of the participants are familiar with the term PPE. Majority assume that health care professionals are given enough safety precautions while treating a patient with coronavirus.Conclusion Hence, to conclude, health care professionals play a vital role in improving access and quality health care for the population, and hence, they must be protected as well. Since dental students treat patients, they are vulnerable to infection as well, and must take proper safety measures.
Keywords: coronavirus; dental students; health care workers; safety measures